The effect of long non-coding RNAs in joint destruction of rheumatoid arthritis - Zhao, Hanxiao; Li, Li; Zhao, Ning; Lu, Aiping; Lu, Cheng; He, Xiaojuan (Frontiers in Cell and Developmental Biology, 2022)
Rheumatoid arthritis (RA) is a systemic autoimmune disease accompanied with joint destruction. Serious joint destruction will eventually lead to disability and the decline of life quality in RA patients. At present, the therapeutic effect of drugs to alleviate joint destruction in RA is limited. Recently, accumulating evidences have shown that long non-coding RNAs (lncRNAs) play an important role in the pathogenesis of joint diseases. Therefore, this paper reviews the expression change and the action mechanism of lncRNAs in joint destruction of RA in recent years. A more comprehensive understanding of the role of lncRNAs in joint destruction will help the treatment of RA.